SURGICAL CONSIDERATION REGARDING MANAGEMENT OF TRICUSPID REGURGITATION IN PATIENTS UNDERGOING MITRAL VALVE SURGERY. - Virwar Kumar Jha (International Journal of Medical Science And Diagnosis Research, 2019)
Background: Severity of tricuspid regurgitation (TR) increases after mitral valve surgery in many patients who do not undergo surgical intervention, causing functional limitation. A redo-cardiac surgery for late severe Function Tricuspid regurgitation is uniformly associated with poor prognosis and high early and late mortality. Concomitant tricuspid repair with mitral valve surgery is recommended and accepted in cases of severe functional TR but its utility for moderate TR remains a dilemma. In such cases, the surgical management is controversial primarily because of uncertainty over the long-term course and clinical sequelae of tricuspid regurgitation after left sided valve surgery; and the diagnostic challenges presented by this very dynamic dysfunction. Thus, this study was done to assess the usefulness of tricuspid annuloplasty concomitant with mitral valve surgery in patients of moderate functional tricuspid regurgitation secondary to rheumatic mitral valve disease. Methods: A Prospective randomized analytical study was done on 50 patients who were divided into two groups. In 25 patient (group 1) mitral valve replacement and tricuspid annuloplasty was done. In 25 patient (group 2) only mitral valve replacement was done. Preoperative, intraoperative, post-operative and follow up parameters in two group was tabulated in excel sheet. Descriptive statistics was analyzed with Statistical Package for Social Sciences (SPSS) version 21.0. p<0.05 was taken as significant. Results: At one year follow up, group 1 patients were symptomatically better than group 2. In group 1, no patient had severe tricuspid regurgitation at any follow up. In group 2, 13.04% of patient had severe tricuspid regurgitation at 1 year follow up (p=0.019). One year survival rate was comparable in both the groups (p>0.05). Conclusion: Moderate functional tricuspid regurgitation with rheumatic mitral valve disease can be managed by concomitant tricuspid repair and mitral valve replacement. Keywords: tricuspid regurgitation, mitral valve, concomitant.